Pathological and immunological evaluation of different regimens of praziquantel treatment in a mouse model of Schistosoma mansoni infection. - Ulrich Membe Femoe; Hermine Boukeng Jatsa; Valentin Greigert; Julie Brunet; Catherine Cannet; Mérimé Christian Kenfack; Nestor Gipwe Feussom; Joseph Bertin Kadji Fassi; Emilenne Tienga Nkondo; Ahmed Abou-Bacar; Alexander Wilhelm Pfaff; Théophile Dimo; et al. (Public Library of Science (PLoS), 2022)
Background One of the considerable challenges of schistosomiasis chemotherapy is the inefficacy of praziquantel (PZQ) at the initial phase of the infection. Immature schistosomes are not susceptible to PZQ at the curative dose. Here, we investigated the efficacy of different PZQ regimens administered during the initial stage of Schistosoma mansoni infection in mice. Methodology/principal findings Two months-old mice were individually infected with 80 S. mansoni cercariae and divided into one infected-untreated control group (IC) and four PZQ-treated groups: PZQ at 100 mg/kg/day for five consecutive days (group PZQ1), PZQ at 100 mg/kg/day for 28 days (group PZQ2), PZQ at 18 mg/kg/day for 28 days (group PZQ3) and a single dose of PZQ at 500 mg/kg (group PZQ4). The treatment started on day one post-infection (p.i), and each group of mice was divided into two subgroups euthanized on day 36 or 56 p.i, respectively. We determined the mortality rate, the parasitological burden, the hepatic and intestinal granulomas, the serum levels of Th-1, Th-2, and Th-17 cytokines, and gene expression. The treatment led to a significant (p < 0.001) reduction of worm burden and egg counts in the intestine and liver in groups PZQ2 and PZQ3. On 56th day p.i, there was a significant reduction (p < 0.001) of the number and volume of the hepatic granulomas in groups PZQ2 and PZQ3 compared to group PZQ1 or PZQ4. Moreover, in group PZQ3, the serum levels of IFN-γ, TNF-α, IL-13, and IL-17 and their liver mRNA expressions were significantly reduced while IL-10 and TGF-β gene expression significantly increased. The highest mortality rate (81.25%) was recorded in group PZQ2. Conclusion/significance This study revealed that the administration of PZQ at 18 mg/kg/day for 28 consecutive days was the optimal effective posology for treating S. mansoni infection at the initial stage in a murine model.